[OP.1A.10] CIRCULATING LEVELS OF PCSK9 AND ARTERIAL STIFFNESS IN A LARGE POPULATION SAMPLE: DATA FROM THE BRISIGHELLA HEART STUDY. (September 2017) - Cicero, A.F.G.; Ruscica, M.; Ferri, N.; Fogacci, F.; Rosticci, M.; Botta, M.; Marchiano, S.; Magni, P.; D'Addato, S.; Giovannini, M.; Borghi, C.
Abstract : Objective: Proprotein convertase subtilisin kexin type 9 (PCKS9) circulating levels are significantly associated with increased risk of total cardiovascular events. Risk markers for cardiovascular diseases (CVD) include parameters relative to arterial structure and function. Our study aimed to evaluate the relationship between circulating levels of PCSK9 and arterial stiffness in a large sample of overall healthy subjects. Figure. No caption available. Design and method: From the historical cohort of the Brisighella Heart Study, four subgroups were selected; pre-menopausal women (n = 227), age-matched men (n = 193), post-menopausal women (n = 460) and age-matched men (n = 416). In these subjects, the correlation between PCSK9 plasma circulating levels and the pulse wave velocity (PWV) was evaluated. Active smokers, participants in secondary prevention for CVD treated with statins or vasodilating agents, were excluded from the analysis. Results: Post-menopausal women showed higher PCSK9 levels (309.9 ± 84.1 ng/mL) compared to the other groups of subjects (p < 0.001). Elderly men had significant higher levels of PCSK9 than adult men (283.2 ± 75.6 ng/mL vs. 260.9 ± 80.4 ng/mL; p = 0.008) (Figure 1). PWV was mainly predicted by age (B = 0.116, 95%CI 0.96 – 0.127, p < 0.001), PCSK9 (B = 0.014, 95%CI 0.011–0.016, p < 0.001), and serum uric acid (B = 0.313, 05%CI 0.024–0.391, p = 0.026). Physical activity, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and estimated glomerular filtration rate were not associated to the PWV level (p > 0.05). Considering the above described subgroups, age and PCSK9 resulted the main factors associated to PWV; the latter correlates to serum uric acid only in post-menopausal women. Conclusions: In the Brisighella Heart Study cohort, circulating PCSK9 are significantly related to the arterial stiffness, independently from gender and menopausal status.